The Juridical Analysis in Viewing the Position of Reported Revocation of Complaints A General Criminal One Party by the Reporter in Investigation Process - Pudjiyanto Pudjiyanto; Arpangi Arpangi; Peni Rinda Listyawati (Law Development Journal, 2022)
This study aims to determine and analyze the legal impact of the unilateral revocation of general crime reports by the reporter at the Semarang Police Station. To find out and analyze the obstacles faced and solutions to unilaterally revocation of reports of general crimes by the reporter at the Semarang Police Station. The research approach method used is legal research analytical descriptive. Based on the research it can be concluded that with the boundaries of the legal field being blurred, it often makes people, most of whom do not understand the law in the criminal and civil spheres, so that all problems are reported or reported to the police. These societal dynamics often result in the revocation of police complaints that are increasingly high in the community as a result of which the issue of legal certainty in the legal process becomes a new boomerang in Indonesia.